MATRIKS VISUALISASI PLOTTING KENDARAAN PADA SISTEM CUSTOMER ORDER (TRUCKING) DI PT. BUANA CENTRA SWAKARSA (2018) - Rehulina Tarigan (Jurnal Sistem Informasi dan Informatika (Simika), 2018)
In the business of transportation, accurate information about the availability of vehicles at a time is very important. This is closely related to the quality of service to customers in terms of order fulfillment, whether the customer's order can be met or served well or not.There are 2 parts that serve to serve the needs of customers, namely the marketing and transportation operations. The marketing always tries to find new customers or retain existing customers by providing the best service: cargo customers can be transported in accordance with the number of vehicles required and in accordance with the agreed schedule. The operationaltransportation undertakes the scheduling of vehicle, vehicle plotting and drivers. In addition, transportation operations should be able to provide correct data or information about the availability of vehicles to marketing. If the data is inaccurate, it can lead to internal conflicts between the two parties. For example, marketing has promised 10 vehicles to fulfill the customer's order at one time, but when the cargo of the customer has to be transported, the number of vehicle is insufficient. A visualization matrix is ​​needed to answer the problem.By looking at the matrix, then all parties will know how many units of vehicles are available at a time, so that the transport of customer cargo can be planned better